Pemberdayaan Masyarakat Desa Wakah, Kecamatan Ngrambe melalui Pembuatan Pakan Lele Alternatif dari Ampas Tahu dan Probiotik - Wachidatul Linda Yuhanna; Yahya Ganda Yulistiana (Institut Pertanian Bogor, 2017)
Wakah Village, Ngrambe Subdistrict is one of catfish farming village in Ngawi District. The obstacles faced by catfish farmers are the high price of feed, thus increasing the cost of production, and also capital. Catfish farmers have not been using alternative feed and still rely on pellet which is produced by factories. Alternative solutions that can be done is to make pellets from local ingredients such as tofu-lees and probiotics. The purpose of this program is to empower Wakah community in making alternative catfish feed of tofu-lees and probiotics. The methods used are the preparation of the program, the manufacturer of the product and the proximate analysis, the making of tutorials videos and guide books, socialization and training, mentoring, monitoring, and evaluating. The result of society's empowerment is catfish farmers in the group Margo Rukun has potential ability to develop fish pellets from the tofu-lees and probiotics. Proximate analysis of fish pellets from tofu and probiotics showed a 32.6% protein, 6.2% fat, 4.5% reducing sugar, 4.8% crude fiber, and 0.3% Ca mineral. Video tutorials and guide books talking about fish pellets made of tofu-lees and probiotics are able to be used by society. Catfish farmers in group Margo Rukun have an ability in making pellets from tofu-lees and probiotics independently with the percentage of material achievement is 80% of the total number of group members. The difficulties which are faced by the farmers during breeding the catfish are weather, supporting material, and marketing. The result of monitoring and evaluation show that catfish farmers Margo Rukun is committed to developing fish pellets from tofu-lees and probiotics as the effort of program sustainability.